Disturbed ventricular-arterial coupling and increased left atrial stiffness in a patient with heart failure with preserved ejection fraction and hyperaldosteronism: a case report. Issue 4 (28th September 2019) - Meyhöfer, Svenja; Schmid, Sebastian M; Hohl, Mathias; Reil, Jan-Christian
Abstract: Background: Aldosterone is involved in almost all parts of the cardiovascular system. Hyperaldosteronism causes arterial hypertension and might predispose to stroke, atrial fibrillation, and heart failure. Case summary: A 60-year-old obese woman with long-standing hypertension, hypokalaemia, and shortness of breath was admitted to our hospital. Hypertension was caused by primary hyperaldosteronism due to an adenoma of the adrenal gland. Detailed transthoracic echocardiography revealed diastolic dysfunction, disturbed ventricular–arterial interaction, and atrial compliance resulting in heart failure with preserved ejection fraction (HFPEF). Three months of aldosterone antagonist treatment improved ventricular–arterial coupling, while left ventricular diastolic and atrial dysfunction remained unchanged. Discussion: Presumably, hyperaldosteronism is the reason for HFPEF in this case. Standard criteria to diagnose HFPEF include clinical symptoms of heart failure and an ejection fraction (EF) >50% as well as echocardiographically or invasively assessed elevated filling pressures. Single beat pressure-volume analysis gives insights on the pathophysiology of increased filling pressures, showing in our case diastolic dysfunction as well as disturbed ventricular–arterial interaction. Three months of aldosterone antagonist treatment reduced blood pressure with concomitant improvement of ventricular–arterial interaction, thereby reducing stroke work while stroke volume remained nearly unchanged. Diastolic dysfunction and increased atrial stiffness were unaltered.